Designing Board Games as an Enhancer of A Sense of Community and Cognition for The Elderly of Tresna Werdha Budi Pertiwi Social Care - Amaliani, Ragil Nahya; Soewardikoen, Didit Widiatmoko; Azhar, Hanif; Rahman, Yanuar (Advances In Social Humanities Research, 2025)
The elderly population often experiences a decline in social interaction and cognitive function, especially in institutional settings such as the Tresna Werdha Budi Pertiwi Social Home in Bandung. Residents frequently face isolation and reduced mental stimulation, which impairs their emotional well-being and independence. This study aims to design a board game that enhances social togetherness and improves cognitive ability among older women in the institution. Using a Design Thinking methodology, researchers engaged in five stages: empathize (through interviews and observations), define (via SWOT analysis and crossover), ideate (sketching concepts and mind mapping), prototype (creating physical mock-ups), and test (evaluating usability with real users). The final product, titled "ABC Brain Teaser," features bright, high-contrast visuals and simple but challenging rules tailored to older people’s preferences and cognitive capabilities. Testing revealed that participants found the game engaging, easy to use, and beneficial for memory stimulation and interaction. The board game effectively addressed the lack of communal activity and provided an inclusive tool for cognitive exercise. This research offers a replicable model for elderly care institutions seeking non-pharmacological interventions to enhance life quality, demonstrating that board games can be both therapeutic and socially empowering when designed with empathy and local context in mind.